(untitled) (Periphērica: Revista de Historia Social, Cultural, y Literaria, 2022)
Clients of corrupt patrons experience a process of moral disintegration, but more importantly, they are instrumental in perpetuating the lack of accountability and corruption. The two film adaptations analyzed here, as well as Luis Estrada’s dark comedies, La ley de Herodes (1999), Un mundo maravilloso (2006), El infierno (2010), and Dictadura perfecta (2014), visualize these informal practices of moral and political submission as hand-kissing, exposing their ritualistic and physical nature. The two film adaptations I study here radically change their literary sources to portray sympathetic characters who submit themselves enthusiastically to a corrupt patron: Arráncame la vida (2008) and El crimen del padre Amaro (2002). The protagonists seek out patrons in order to get access to power and its benefits. The changes that filmmakers made illuminate the practice of clientelism: political subordination in exchange for material advantages, perceived as friendship or fictive kinship.